Boryl Radical-Promoted Deoxygenative Alkylation of Benzyl Acetates - Liu, Nan-Nan; Wan, Xuan-Chen; Hui, Li-Wen; Zhang, Feng-Lian; Wang, Yi-Feng (Synthesis, 2023)
Deoxygenative alkylation of benzyl alcohols was realized by using acetate as the alcohol activation group. The C–O bond homolysis is achieved by a boryl radical-promoted β-scission process. The strategy is amenable to a variety of benzyl alcohols, including primary, secondary, and more challenging tertiary alcohols. The synthetic practicability was demonstrated by a gram-scale one-pot reaction.
Keywords: deoxygenative alkylation; C–O bond activation; reduction; boryl radical